Development of animation video assistant teaching science courses in SD Negeri 056 Lamasariang - P. Purnama; P. Pattaufi; Nurhikmah H (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
This development research focuses on making teaching materials in animated videos for science subjects at SDN 056 Lamasariang. Science subjects at SDN 056 Lamasariang. This research aims to improve learning effectiveness using an exciting visualization approach for students. This research uses technology and animation media to increase the involvement of students in the learning process, especially in learning process science subjects. Besides, it can help learners understand complex concepts that can be easily understood. The research method used is Research and Development with the ADDIE development model, which consists of 5 stages: analysis, design, development, implementation, and evaluation. The results showed that teaching materials based on animated videos are very effective in applying Class V science subjects, as seen from the acquisition of learning outcomes before (pretests) and after (posttest). The conclusion is that the results of developing teaching materials based on animated videos fulfill effective use in the learning process. AbstrakPenelitian ini merupakan penelitian pengembangan yang berfokus pada pembuatan bahan ajar berupa video animasi untuk mata pelajaran IPA di SDN 056 Lamasariang. Penelitian ini bertujuan untuk meningkatkan efektivitas pembelajaran dengan menggunakan pendekatan visualisasi yang menarik bagi peserta didik. Penelitian ini menggunakan teknologi dan media animasi sehingga dapat meningkatkan keterlibatan peserta didik dalam proses pembelajaran, khususnya dalam mata pelajaran IPA selain itu dapat membantu peserta didik dalam memahami konsep-konsep yang kompleks dan dapat dengan mudah memahami pembelajaran. Metode penelitian yang digunakan yaitu Research and Development dengan model pengembangan ADDIE yang terdiri dari 5 tahapan, yakni: analisis, desain, pengembangan, implementasi dan evaluasi. Hasil penelitian menunjukkan bahwa bahan ajar berbasis video animasi sangat efektif di terapkan pada mata pelajaran IPA Kelas V, dilihat dari perolehan nilai hasil belajar sebelum (pretes) dan sesudah (posttes).Kesimpulannya bahwa hasil pengembangan bahan ajar berbasis video animasi memenuhi efektif digunakan dalam proses pembelajaran.Kata Kunci: Bahan ajar; pengembangan produk pembelajaran; video animasi